The World Health Organization 1973 classification system for grade is an important prognosticator in T1 non‐muscle‐invasive bladder cancer. (27th April 2018) - van de Putte, Elisabeth E. Fransen; Bosschieter, Judith; van der Kwast, Theo H.; Bertz, Simone; Denzinger, Stefan; Manach, Quentin; Compérat, Eva M.; Boormans, Joost L.; Jewett, Michael A.S.; Stoehr, Robert; van Leenders, Geert J.L.H.; Nieuwenhuijzen, Jakko A.; et al.
Abstract : Objectives: To compare the prognostic value of the World Health Organization (WHO) 1973 and 2004 classification systems for grade in T1 bladder cancer (T1‐BC), as both are currently recommended in international guidelines. Patients and Methods: Three uro‐pathologists re‐revised slides of 601 primary (first diagnosis) T1‐BCs, initially managed conservatively (bacille Calmette–Guérin) in four hospitals. Grade was defined according to WHO1973 (Grade 1–3) and WHO2004 (low‐grade [LG] and high‐grade [HG]). This resulted in a lack of Grade 1 tumours, 188 (31%) Grade 2, and 413 (69%) Grade 3 tumours. There were 47 LG (8%) vs 554 (92%) HG tumours. We determined the prognostic value for progression‐free survival (PFS) and cancer‐specific survival (CSS) in Cox‐regression models and corrected for age, sex, multiplicity, size and concomitant carcinoma in situ . Results: At a median follow‐up of 5.9 years, 148 patients showed progression and 94 died from BC. The WHO1973 Grade 3 was negatively associated with PFS (hazard ratio [HR] 2.1) and CSS (HR 3.4), whilst WHO2004 grade was not prognostic. On multivariable analysis, WHO1973 grade was the only prognostic factor for progression (HR 2.0). Grade 3 tumours (HR 3.0), older age (HR 1.03) and tumour size >3 cm (HR 1.8) were all independently associated with worse CSS. Conclusion: The WHO1973 classification system for grade has strong prognostic value in T1‐BC, compared to the WHO2004 system. Our present results suggest that WHO1973 grade cannot be replaced by the WHO2004 classification in non‐muscle‐invasive BC guidelines.